Efficient substrates based on anaerobic sewage sludge biochar for tobacco seedlings in floating systems. - MONTEIRO, A. B. (2022)
The objective was to develop efficient substrates, with increasing proportions of biochar derived from anaerobic sewage sludge (ASS-biochar) and regionally available raw materials, to produce tobacco seedlings (Nicotiana tabacum) in floating systems. Physical, hydraulic and chemical variables and the effects on tobacco plants were evaluated through an indoor experiment with seedling production. The experiment was conducted on trays in a floating hydroponic system in a randomized block design with four replications and eight plants per plot. The ASS-biochar showed environmental safety and agronomic efficiency in substrate composition, in particular with 50% to 90% ASS-biochar in the formulation. The best formulations positively affected the growth-related variables, showing similar or superior performance to the three commercial substrates (references). The ideal ranges of the substrate characteristics were: dry density: 420?520 kg m?3; total porosity: 60?75%; aeration space: 25?35%; easily available water: 9?12%; water buffering capacity: 3?5%; available water: 12?15%; remaining water: 20?25%; pH: 6.0?6.5; electrical conductivity: 1.4?2.3 mS cm?1. The development of substrates considering ASS-biochar, regional raw materials and ideal physical-chemical properties would prevent environmental pollution by generating value-added products to improve tobacco seedlings and expand the productivity and quality of tobacco worldwide.